Leaf, Anthocyanin, and Protein Production of Talinum triangulare Jacq. Willd with Various Rates of P Fertilizer - Leo Mualim (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
The effect of P fertilizer rates on growth and production parameters of waterleaf [Talinum triangulare (Jacq.) Willd] were studied over two months (February-April 2010) in Bogor. Treatments of fi ve P-rates (0, 200, 400, 600, and 800 kg SP- 18 ha-1) were laid out in a randomized complete block design with three replications. Generally, the effect of P fertilization in waterleaf was mostly prominent at 8th week after planting (WAP). The increase of P rates increased leaf area, leaf fresh weight, edible part (shoot weight), and protein production; but decreased anthocyanin production. These results suggested that to produce high protein and anthocyanin, waterleaf must be fertilized with 400 kg SP-18 ha-1; and P fertilizer must be applied at least two weeks before planting. Keywords: inorganic fertilizer, phosphorus, portulacaceae, secondary metabolite